Plasmin and regulators of plasmin activity control the migratory capacity and adhesion of human T cells and dendritic cells by regulating cleavage of the chemokine CCL21. Issue 10 (2nd August 2016) - Lorenz, Natalie; Loef, Evert Jan; Kelch, Inken D; Verdon, Daniel J; Black, Moyra M; Middleditch, Martin J; Greenwood, David R; Graham, E Scott; Brooks, Anna ES; Dunbar, P Rod; Birch, Nigel P
Abstract : The homeostatic chemokine CCL21 has a pivotal role in lymphocyte homing and compartment localisation within the lymph node, and also affects adhesion between immune cells. The effects of CCL21 are modulated by its mode of presentation, with different cellular responses seen for surface‐bound and soluble forms. Here we show that plasmin cleaves surface‐bound CCL21 to release the C‐terminal peptide responsible for CCL21 binding to glycosaminoglycans on the extracellular matrix and cell surfaces, thereby generating the soluble form. Loss of this anchoring peptide enabled the chemotactic activity of CCL21 and reduced cell tethering. Tissue plasminogen activator did not cleave CCL21 directly but enhanced CCL21 processing through generation of plasmin from plasminogen. The tissue plasminogen activator inhibitor neuroserpin prevented processing of CCL21 and blocked the effects of soluble CCL21 on cell migration. Similarly, the plasmin‐specific inhibitor α2 ‐antiplasmin inhibited CCL21‐mediated migration of human T cells and dendritic cells and tethering of T cells to APCs. We conclude that the plasmin system proteins plasmin, tissue plasminogen activator and neuroserpin regulate CCL21 function in the immune system by controlling the balance of matrix‐ and cell‐bound CCL21.